Prediction of residual ischemic risk in ticagrelor-treated patients with acute coronary syndrome - Yuting Zou (Thrombosis Journal, 2022)
Abstract Background Despite strong antiplatelet therapy with ticagrelor, serious ischemic events still occur in patients with acute coronary syndrome (ACS). The predictability of platelet reactivity to the residual risk of ischemic events during ticagrelor treatment remains uncertain. Objectives We aimed to investigate the predictability of the thromboelastography (TEG)-measured adenosine disphosphate (ADP)-induced platelet inhibition rate (ADP%) to the ischemic events in ticagrelor-treated patients with ACS. Methods A cohort of ticagrelor-treated patients with ACS were consecutively recruited. ADP% was measured by TEG after 3 days of ticagrelor maintenance treatment. The primary ischemic event was defined as rehospitalization for unstable angina (UA) within 1 year, and the secondary ischemic event was a composite of the primary ischemic event plus all-cause death, nonfatal myocardial infarction (MI), stent thrombosis, stroke, and unplanned revascularization within 1 year. Results A total of 751 eligible patients with ACS were included in the analysis, with 336 patients randomly assigned to the derivation group and 415 to the validation group. The overall rates of primary and secondary ischemic events were 14.51% (n = 109) and 16.91% (n = 127), respectively. Compared to the patients without ischemic events, those with ischemic events had a significantly lower ADP% both in the derivation group (for primary ischemic events: 66.05% vs. 92.80%, p < 0.001; for secondary ischemic events: 66.05% vs. 93.20%, p < 0.001) and in the validation group (for primary ischemic events: 66.40% vs. 89.20%, p < 0.001; for secondary ischemic events: 66.90% vs. 89.20%, p < 0.001). Receiver operating characteristic curve (ROC) analysis showed that an ADP% < 76% was the optimal cut-off value for predicting 1-year primary ischemic events, with an area under the curve (AUC) of 0.80 (95% CI: 0.72–0.86, p < 0.001) in the derivation group and 0.77 (95% CI: 0.69–0.85, p < 0.001) in the validation group. The multivariate Cox regression hazard analysis consistently identified an ADP% < 76% as an independent predictor of primary ischemic events in the derivation group (HR: 8.21, 95% CI: 4.82–13.99, p < 0.001) and in the validation group (HR: 6.34 95% CI: 3.32–12.11, p < 0.001). There was also a strong association between an ADP% < 76 and the occurrence of secondary ischemic events in the derivation group (HR: 7.33, 95% CI: 4.47–12.00, p < 0.001) and in the validation group (HR: 4.76, 95% CI: 2.73–8.32, p < 0.001). Conclusion The ADP-induced platelet inhibition rate measured by TEG could predict ischemic events in ticagrelor-treated patients with ACS.